COMMUNICATION: THEORIES AND APPLICATIONS - Redmond Mark V (Houghton Mifflin, 2000)
FUNDAMENTALS OF HUMAN COMMUNICATION CONTEXT AND PRINCIPLES OF COMMUNICATION PERCEIVING, LISTENING AND RESPONDING ATTRIBUTION OF MEANING IN VERBAL AND NONVERBAL COMMUNICATION
FUNDAMENTALS OF HUMAN COMMUNICATION CONTEXT AND PRINCIPLES OF COMMUNICATION PERCEIVING, LISTENING AND RESPONDING ATTRIBUTION OF MEANING IN VERBAL AND NONVERBAL COMMUNICATION